Shoulder internal and external rotation strength and prediction of subsequent injury in water polo players - Hams, A. H.; Evans, K.; Adams, R.; Waddington, G.; Witchalls, J. (Scandinavian Journal of Medicine & Science in Sports, 2019)
Water polo players have greater isokinetic shoulder strength than age-matched controls. Due to the repetitive demands of throwing, however, water polo players demonstrate an altered strength ratio, with greater internal rotation (IR) strength relative to external rotation (ER). The relationship between shoulder strength and risk of shoulder injury is unknown. In addition, the effect on test position for strength testing on the reliability of hand-held dynamometry (HHD) in this population is not known.